Influence of electrode cooling on material migration among the electrodes during edm of titanium alloy - Abdulkareem, Suleiman; Khan, Ahsan Ali; Mohamed , Konneh (Trans Tech Publications Ltd., Switzerland, 2011)
Electrical discharge machining (EDM) is widely used in the machining of electrically conductive hard metals for the production of dies and moulds. This paper describes an investigation of the effect of electrode cooling on the amount of elements migration from the electrode to the workpiece surface and from the workpiece to the electrode surface. In the present study EDM has been performed with electrodes cooled by liquid nitrogen as well as with electrodes without cooling. Current, pulse-on time, pulse-off time and voltage were taken as the variables during conducting the experiments. The analysis on material migration during EDM was carried out by SEM and EDX. It was observed that EDM with liquid nitrogen reduces material migration and minimizes the surface contamination of both the electrodes.